Impact of lockdown and school closure on children in special schools: a single-centre survey - Piriyanga Kesavan; Tapomay Banerjee; Amjad Khan (BMJ Publishing Group, 2021)
Special schools play a significant role in the daily lives of children and young people with special educational needs and disabilities. We explored the impact of the COVID-19-related first lockdown and resulting school closure by surveying parents whose children attended three special schools in Bedford, UK. We asked about anxiety and impact on emotional well-being and education. We received 53 responses from parents: 31 felt their child was more anxious during the lockdown period/school closure compared with beforehand and 42 felt their child's emotional well-being had been affected. Children and young people attending special schools may have struggled both academically and emotionally during the COVID-19 pandemic.